1998
DOI: 10.1006/dbio.1998.9037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Two Series of Ca2+Oscillations in Activation of Ascidian Eggs

Abstract: Changes in [Ca2+]i are an essential factor regulating egg activation. Matured ascidian eggs are arrested at metaphase I, and two series of [Ca2+]i transients have been observed after fertilization: Ca2+ waves just after fertilization (Series I) and [Ca2+]i oscillation between the first and second polar body extrusion (Series II). We investigated mechanisms involved in the elevation of [Ca2+]i and the role of the [Ca2+]i transients during egg activation in Ciona savignyi. The monoclonal antibody 18A10 against I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 63 publications
2
51
0
Order By: Relevance
“…Purification and identification of the IP 3 R protein from the cerebellum occurred in the late 1980s (Maeda et al 1988; Furuichi et al 1989), and confirmation of its significance in mammalian fertilization took place soon after when both the initiation of [Ca 2þ ] i oscillations (Miyazaki et al 1992) and egg activation (Xu et al 1994) were prevented by injection of a functional blocking antibody raised against the Carboxy-terminal end of mouse IP 3 R1. Subsequent studies confirmed the role of IP 3 R1 in fertilization in other species (Parys et al 1994;Thomas et al 1998;Yoshida et al 1998;Runft et al 1999;Goud et al 2002;Iwasaki et al 2002).Fertilization-associated [Ca 2þ ] i oscillations in mouse zygotes undergo changes during the transition from the MII stage into interphase, becoming initially less frequent before ceasing altogether at the time of PN formation (Jones Kono et al 1996; Deguchi et al 2000). During this transition, the IP 3 R1 undergo several modifications and it is possible that either singly or collectively these influence the pattern of oscillations.…”
mentioning
confidence: 84%
“…Purification and identification of the IP 3 R protein from the cerebellum occurred in the late 1980s (Maeda et al 1988; Furuichi et al 1989), and confirmation of its significance in mammalian fertilization took place soon after when both the initiation of [Ca 2þ ] i oscillations (Miyazaki et al 1992) and egg activation (Xu et al 1994) were prevented by injection of a functional blocking antibody raised against the Carboxy-terminal end of mouse IP 3 R1. Subsequent studies confirmed the role of IP 3 R1 in fertilization in other species (Parys et al 1994;Thomas et al 1998;Yoshida et al 1998;Runft et al 1999;Goud et al 2002;Iwasaki et al 2002).Fertilization-associated [Ca 2þ ] i oscillations in mouse zygotes undergo changes during the transition from the MII stage into interphase, becoming initially less frequent before ceasing altogether at the time of PN formation (Jones Kono et al 1996; Deguchi et al 2000). During this transition, the IP 3 R1 undergo several modifications and it is possible that either singly or collectively these influence the pattern of oscillations.…”
mentioning
confidence: 84%
“…In the case of square pulse Ca 2+ release, η(t) = ηΘ(t)Θ(∆ − t), we can explicitly compute its value, because calculating the travelling wave solution from (41)(42)(43)(44) respectively, with corresponding eigenvalues λ i , we may write G(ξ) = P e Λξ P −1 where…”
Section: A Conserved Quantity In the Co-moving Framementioning
confidence: 99%
“…The first two of these mechanisms have been proposed to be responsible for Ca 2+ waves observed in the immature Xenopus laevis oocyte, while the third mechanism seems to describe the fertilization Ca 2+ wave in the mature Xenopus egg. Interestingly, when the local dynamics of Ca 2+ release and reuptake are spatially heterogeneous, one-dimensional continuum models (1) are also able to produce a fourth wave phenomenon in which fronts of elevated intracellular [Ca 2+ ] propagate in a back-and-forth manner that resembles the movement of tango dancers (40) and is reminiscent of the behavior of Ca 2+ waves in nemertean worm (41) and ascidian eggs (42). While spatial heterogeneity of model parameters may give rise to these socalled 'tango waves', the phenomenon can also be observed in models with spatially homogeneous parameters as long as the initial concentration profiles are chosen so that an auxilary variable known as the total [Ca 2+ ] given by…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it may be that, although the NO pathway itself is widely distributed (52)(53)(54), its involvement at fertilization is confined to echinoderms or perhaps echinoids. Neither frog (55), ascidian (56), nor mammalian oocytes (57, 58) rely on the RyR receptor at fertilization, and neither mouse nor ascidian oocytes showed any evidence of increases in NO at fertilization (27). One obvi- The mean latent period (ϮS.E.…”
Section: Measurements Of Cadpr Levels At Fertilization Suggest Cadpr mentioning
confidence: 99%